2016
DOI: 10.3346/jkms.2016.31.10.1624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Deprivation on the Male Reproductive System in Rats

Abstract: There has been no study reporting on the influence of sleep deprivation on the male reproductive system including sperm quality. In this study, we hypothesized that sleep deprivation could lead to adverse effect on the male reproductive system. The rats were divided into three groups: 1) control (home-cage, n = 10); 2) SD4 (sleep deprivation for 4 days, n = 10); and 3) SD7 (sleep deprivation for 7 days, n = 10). Sleep deprivation was performed by a modified multiple platform method. Sperm quality (sperm motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…In fact, it is know that ACTH and cortisol release can lead to an oxidative stress state, 15 and these alterations could play a pivotal role in PSD-induced behavioral changes. 40,44 As Li was able to reduce ACTH and cortisol release induced by PSD, it is possible that, in the present study, the effects of Li on oxidative stress may have been mediated, at least in part, by ACTH and cortisol modulation.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In fact, it is know that ACTH and cortisol release can lead to an oxidative stress state, 15 and these alterations could play a pivotal role in PSD-induced behavioral changes. 40,44 As Li was able to reduce ACTH and cortisol release induced by PSD, it is possible that, in the present study, the effects of Li on oxidative stress may have been mediated, at least in part, by ACTH and cortisol modulation.…”
Section: Discussionmentioning
confidence: 69%
“…Suchecki and colleagues showed that PSD induced using different methods increased ACTH and corticosterone secretion. Indeed, insomnia is associated with increases of ACTH and cortisol secretion, and activation of the HPA axis or administration of glucocorticoids can lead to arousal and sleeplessness …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothalamus via a system of releasing hormones regulates the actions of the pituitary gland which secretes many tropic hormones including LH; LH in turn stimulates Leydig cells to secrete testosterone. Free circulating testosterone promotes spermatogenesis through its stimulatory effects on Sertoli cells in the seminiferous tubules [28,32,33]. In effect, increase in circulating levels of testosterone is shown to be correlated with increased epididymal sperm count while LH only promotes testicular development [34].…”
Section: Effect Of Polyscias Fruticosa On Male Fertilitymentioning
confidence: 93%
“…Improvement in weight and size of reproductive structures such as testis and seminiferous tubules are directly related to normal male sexual development [28]. In effect, increase in weight of reproductive organs secondary to drug treatments indicates that perhaps such agents may improve reproductive processes including spermatogenesis.…”
Section: Effect Of Polyscias Fruticosa On Male Fertilitymentioning
confidence: 99%